In silico study to predicting Apyrase-ADP binding affinity from salivary gland of Aedes aegypti in inhibition of platelet aggregation by molecular docking - Kartika Senjarini; Rike Oktarianti; Silvya Fitri Nur Azizah; Ari Satia Nugraha; Syubbanul Wathon (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.